Mass wasting on Phobos triggered by an evolving tidal environment. Issue 24 (26th December 2016) - Shi, X.; Oberst, J.; Willner, K.
Abstract: The Martian moon Phobos is experiencing orbital decay, increasing tidal forces, and possible disruption in the near future. We suggest that this changing dynamic tidal environment has contributed to resurfacing of the odd‐shaped small moon. We investigated mass wasting features in craters using high‐resolution images acquired by the Mars Express on board High‐Resolution Stereo Camera. We model the evolving dynamical environment of Phobos by reconstructing dynamic slopes on its surface with Phobos at different distances to Mars. We note that the increase in slope by tidal effect correlates with most of the observed landslides, which is particularly obvious for craters near the sub‐Mars and anti‐Mars points. We suggest that the effect has triggered mass displacements that are responsible for observed asymmetries of some craters. The most recent landslides are likely to be geologically young and occurred within the past few hundred million years. Key Points: Phobos' dynamical environment is affected by intensifying tidal forces over the past billion years Mass wasting features observed in Mars Express HRSC images correlate with areas where dynamic slopes are increasing Landslides in craters appear to be young and to have occurred in the past few hundred million years